2014
DOI: 10.1177/0960327114538986
|View full text |Cite
|
Sign up to set email alerts
|

Can initial lactate levels predict the severity of unintentional carbon monoxide poisoning?

Abstract: Introduction: Accidental carbon monoxide (CO) intoxication is a major cause of unintentional poisoning. This study aimed to determine the value of initial lactate levels in patients with CO poisoning and to evaluate its utilization in the emergency department (ED). Methods: A retrospective cross-sectional study was carried out among patients with CO intoxication, who were admitted to the ED between April 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 18 publications
3
18
0
Order By: Relevance
“…Cervellin et al (11) and Icme et al (15) reported a more significant lactate increase among patients treated with HBOT. Doğan et al (9) found higher lactate levels in patients with mental status changes and the need for HBOT compared to those without; they also reported an AUC level of 0.83 for plasma lactate levels in predicting HBOT need (9). In agreement with the literature, we found a higher admission plasma lactate level among patients that received HBOT and found an AUC value of 0.708 for predicting HBOT need.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Cervellin et al (11) and Icme et al (15) reported a more significant lactate increase among patients treated with HBOT. Doğan et al (9) found higher lactate levels in patients with mental status changes and the need for HBOT compared to those without; they also reported an AUC level of 0.83 for plasma lactate levels in predicting HBOT need (9). In agreement with the literature, we found a higher admission plasma lactate level among patients that received HBOT and found an AUC value of 0.708 for predicting HBOT need.…”
Section: Discussionsupporting
confidence: 89%
“…The efficacy of lactate clearance for treatment guidance in sepsis has led to the performance of studies to evaluate the feasibility of its use in critically ill patients with systemic involvement due to other diseases (7,8). Although several studies reporting a correlation between initial lactate levels and disease severity in CO exposure have been recently published, there are a limited number of studies examining lactate clearance in CO intoxication (9)(10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%
“…Hyperlactatemia from carbon monoxide toxicity is suspected to result primarily from tissue hypoxia, although mitochondrial dysfunction and catecholamine effects, which will be discussed further in later sections, may also contribute . In keeping with a multifactorial pathogenesis, lactate concentration is variably correlated with carboxyhemoglobin concentrations as well as the duration of carbon monoxide exposure …”
Section: Pathophysiology–dyshomeostasis In Diseasementioning
confidence: 99%
“…22 In keeping with a multifactorial pathogenesis, lactate concentration is variably correlated with carboxyhemoglobin concentrations as well as the duration of carbon monoxide exposure. [117][118][119] Type B1 hyperlactatemia Hyperlactatemia associated with underlying disease: Malignancy A variety of potential mechanisms for malignancyassociated hyperlactatemia have been identified including: increased production of glycolytic enzymes by hypoxia-inducible factors 1 and 2, 120-122 increased production of glycolysis intermediates via upregulation of the pentose phosphate pathway, 22,123 mitochondrial dysfunction, reduced hepatic clearance, and malnutrition causing thiamine deficiency. 12,28 Malignant cells 90 preferentially use glycolytic pathways despite readily available oxygen, 22,122 and lactate may alter the tumor micro environment in a manner that inhibits destruction of neoplastic cells.…”
Section: Anemia and Hypoxemiamentioning
confidence: 99%
“…
We read with interest the study by Dogan et al 1 and question the authors' interpretation.The study's primary outcome is to determine whether serum lactate correlates with hyperbaric oxygen (HBO) therapy. The main rationale for HBO in carbon monoxide (CO) poisoning is to reduce the risk of delayed neurologic sequelae.

2,3 However, HBO is a treatment modality and not a measurable clinical outcome.

…”
mentioning
confidence: 98%